Cement and oil refining industries as the predominant sources of trace metal pollution in the Red Sea: A systematic study of element concentrations in the Red Sea zooplankton. (January 2022) - Cai, Chunzhi; Devassy, Reny P.; El-Sherbiny, Mohsen M.; Agusti, Susana
Abstract: The Red Sea is exposed to metals from a large variety of natural and anthropogenic sources. In this study, we analyzed 19 common element concentrations in 14 Red Sea zooplankton samples using inductively coupled plasma-optical emission spectrometry (ICP-OES). The average metal or metalloid concentrations of the Red Sea zooplankton were: Ca > Sr > Fe > Al > Zn > As > Cu > Mn > Cr > Mo > Ni > Pb > Cd. The As, Ca, and Cu concentrations significantly increased with increasing latitude, while Cd concentrations decreased ( p < 0.01). Our study indicated that anthropogenic activities (i.e., cement factories and oil refining industries) might be the predominant sources of significantly high Cr (1718 mg/kg), Fe (11, 274 mg/kg), Mn (57.3 mg/kg), Mo (286 mg/kg), Ni (226 mg/kg), Pb (332 mg/kg), and Zn (17, 046 mg/kg) concentrations that recorded in the Central to North Red Sea zooplankton. Graphical abstract: Unlabelled Image Highlights: The Red Sea is a unique environment with multiple metal sources. Copepoda and Gastropod larvae were the dominant zooplankton in the Red Sea. Zooplankton encountered severe metal pollution in the North Red Sea. As, Ca, Cr, and Cu showed clear latitudinal changes in the Red Sea zooplankton. High Al concentrations in the Red Sea zooplankton might be owing to sandstorms.